Translation of Morphologically Complex Terms: The Case of untenantability - Ratkus, Artūras (Vertimo studijos, 2022)
The article addresses problems of understanding and translation of morphologically complex terms, often characterized in terms of idiosyncratic and unpredictable semantics. This is due not only to the complex structural relations within such words, but also the individual history and idiosyncratic lexical properties of their components. The law term untenantability belongs to a motley group of semantically complex derivatives in -able. It is argued that untenantability bears no semantic relation to the modal adjective able. The morphological structure of untenantability and its syntactic properties highlight its meaning of ‘unfit for tenancy’. This meaning is corroborated, and its specifics clarified, by the use of untenantability in legal contexts.
Keywords: word building; derivation; law term; translation; meaning; lease